Isolation of antioxidant enzymes from some wild edible fruits at mature and ripened stage rhizome - Rathod, Sujata Valvi, D.P. Yesane and V.S. (Current Botany, 2011)
<span style="font-size: 8pt; color: black; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IT">The activity of catalase (CAT), peroxidase (POX), superoxide dismutase (SOD), were determined in ten wild edible fruits, viz <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IT">Ficus racemosa <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: IT; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="IT">Linn., Elaeagnus conferta Roxb., Flacourtia indica (Burm. f.)Merr., Glycosmis pentaphylla (Retz.) DC., Ziziphus rugosa Lamk., Meyna laxiflora Robyns., Cordia dichotoma Linn., Grewia tiliifolia Vahl, Scleichera oleosa Merr. and <span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Antidesma ghasembilla<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Gaertn. The CAT and SOD activity was increased in mature fruits than ripened fruits, whereas POX activity found to be more in ripened fruits as compare to mature fruits.